Does an additional structured information program during the intensive care unit stay reduce anxiety in ICU patients?: a multicenter randomized controlled trial - Fleischer, Steffen; Berg, Almuth; Behrens, Johann; Kuss, Oliver; Becker, Ralf; Horbach, Annegret; Neubert, Thomas R (BMC anesthesiology, 2014)
Background Communication and information in order to reduce anxiety in the intensive care unit (ICU) has been described as area needing improvement. Therefore, the aim of this trial was to evaluate whether a structured information program that intensifies information given in standard care process reduces anxiety in ICU patients. Methods Multicenter, two-armed, non-blinded, parallel-group randomized controlled trial in hospitals in the cities of Marburg, Halle, and Stuttgart (Germany). The trial was performed in cardiac surgery, general surgery, and internal medicine ICUs. Two-hundred and eleven elective and non-elective ICU patients were enrolled in the study (intervention group, n = 104; control group, n = 107). The experimental intervention comprised a single episode of structured oral information that was given in addition to standard care and covered two main parts: (1) A more standardized part about predefined ICU specific aspects – mainly procedural, sensory and coping information, and (2) an individualized part about fears and questions of the patient. The control group received a non-specific episodic conversation of similar length additional to standard care. Both conversations took place at the beginning of the ICU stay and lasted 10–15 minutes. Study nurses administered both interventions. The primary outcome ICU-related anxiety (CINT-Score, 0–100 pts., higher scores indicate higher anxiety) was assessed after admission to a regular ward. Results The primary outcome could be measured in 82 intervention group participants and 90 control group participants resulting in mean values of 20.4 (SD 14.4) compared to 20.8 (SD 14.7) and a mean difference of −0.2 (CI 95% -4.5 to 4.1). Conclusions A structured information intervention additional to standard care during ICU stay had no demonstrated additional benefit compared to an unspecific communication of similar duration. Reduction of anxiety in ICU patients will probably require more continuous approaches to information giving and communication. Trial registration ClinicalTrials.gov NCT00764933 .